Measurement of food consumption growth in Vietnamese households: The role of classifying predicted and transitory income shocks by asset accumulation - Ka Son La; Ha Duc Vu (PLoS ONE, 2025)
The study measures the food consumption growth in Vietnamese households by classifying income and assets or consumption habits. The FE, RE, and Sys-GMM methods estimate dynamic data from the VARHS (2008–2018) survey of 1,915 households in 466 communes. The results show heterogeneity in marginal propensities to food consumption growth (MPCs) by asset level and by breaking down income changes (current income, predictable income and transitory income shocks). The MPCs, in response to transitory income shocks, are higher for poorer households than for richer ones. Additionally, classification by growth rates of assets reveals new characteristics in household food consumption growth. For household groups with slower growth rates of assets, the MPCs decrease, and other factors such as asset growth, ethnicity, and household size become more important in explaining food consumption growth, especially for predictable income shocks. Ultimately, food consumption habits do not explain changes in household food consumption growth.